Long‐Term Stability of Minimally Invasive Radial Keratotomy for Mild to Moderate Keratoconus. Issue 5 (September 2017) - Fujimoto, Kahoko; Osawa, Hideya; Moriyama, Takashi; Miyamoto, Takako; Irie, Tomomi; Nishimura, Tetsuya; Inoue, Tomoyuki
Abstract : Purpose: : This study aimed to evaluate the long‐term stability of minimally invasive radial keratotomy (mini‐RK) for eyes with mild to moderate keratoconus. Design: : Retrospective observational case series. Methods: : Eleven eyes from 6 patients with hard contact lens (HCL)‐intolerant keratoconus underwent mini‐RK and were followed up for more than 5 years. The mini‐RK consisted of 8 radial incisions with depths of 90% of the thinnest corneal thickness, based on the Lindstrom nomogram. Best‐corrected visual acuity (BCVA), keratometry, and corneal endothelial cell density (ECD) were examined preoperatively and for 5 to 10 years postoperatively. Changes in keratometric astigmatism were evaluated using power vector analysis. Severities of keratoconus preoperatively and 1 year postoperatively were graded using the Amsler‐Krumeich classification. Results: : The postoperative observation periods were from 6 to 10 years (mean, 7.9 years). There were no changes in the BCVA, ECD, and keratometric astigmatism. The mean keratometric refraction significantly decreased from 47.5 diopters (D) preoperatively to 44.0 D at 1 month after mini‐RK ( P = 0.037) and was stable over 5 years, whereas keratometric astigmatism did not change from the preoperative through the postoperative period ( P > 0.59). Keratoconus of grade 2 or higher improved to lower grades. Conclusions: : The mini‐RK treatment was safe and effective for HCLintolerant eyes with mild to moderate keratoconus.